Magnetophoretic Sorting of Single Catalyst Particles. (12th July 2018) - Solsona, Miguel; Nieuwelink, Anne‐Eva; Meirer, Florian; Abelmann, Leon; Odijk, Mathieu; Olthuis, Wouter; Weckhuysen, Bert M.; van den Berg, Albert
Abstract: A better understanding of the deactivation processes taking place within solid catalysts is vital to design better ones. However, since inter‐particle heterogeneities are more a rule than an exception, particle sorting is crucial to analyse single catalyst particles in detail. Microfluidics offers new possibilities to sort catalysts at the single particle level. Herein, we report a first‐of‐its‐kind 3D printed magnetophoretic chip able to sort catalyst particles by their magnetic moment. Fluid catalytic cracking (FCC) particles were separated based on their Fe content. Magnetophoretic sorting shows that large Fe aggregates exist within 20 % of the FCC particles with the highest Fe content. The availability of Brønsted acid sites decreases with increasing Fe content. This work paves the way towards a high‐throughput catalyst diagnostics platform to determine why specific catalyst particles perform better than others.